Hardness Comparison of Single-Shade vs Multi-Shade Dental Resin Nano-Composite - Nuradnin, Ananda Haura; Mozartha, Martha; Kesumaputri, Bebbi Arisya; Anastasia, Danica (Insisiva Dental Journal: Majalah Kedokteran Gigi Insisiva, 2024)
Shade matching of multi-shade dental resin nano-composite is a process that requires time and operator expertise. Single-shade universal composite resin claimed to match all tooth colors to simplify the process. Comprehensive testing, including an assessment of surface hardness, is needed to evaluate the properties of this relatively new single-shade universal composite and to evaluate the surface hardness of single-shade universal composite compared to multi-shade dental resin nano-composite. This experimental study tested two composite restorative materials: single-shade universal composite (Omnichroma, Tokuyama Dental, Japan) and nanofilled composite resin (FiltekTM Z350 XT, 3M/ESPE, USA). Thirty specimens divided into 2 groups (n=15) were fabricated by placing the composites into a stainless steel mold (2 mm thick × 12 mm diameter) and photoactivated for 20 seconds, followed by finishing and polishing. Surface hardness was evaluated using a Vickers hardness testing machine and a diamond indenter with a load of 1000 g applied for 15 seconds. Data were analyzed by using an independent t-test. The mean surface hardness of single-shade universal and multi-shade dental resin nano-composite were 21.04±4,92 and 19.33±5,61 Vickers hardness number (VHN), respectively. Single-shade universal composite showed no significant difference in surface hardness to multi-shade dental resin nano-composite (p-value > 0.05). The surface hardness value of single-shade universal composite resin was comparable to multi-shade dental resin nano-composite.